A Growth of Cocoa, Trinidad - (:unkn) unknown (Wilsons Limited, 2010)
A picture of a cocoa tree with its fruit attached to the trunk.
Colour: Coloured; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cacao--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Theobroma--Trinidad and Tobago